Norm Compliance in an Uncertain World - Toke Reinholt Fosgaard; Lars Gårn Hansen; Erik Wengström (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2020)
In many situations, social norms govern behavior. While the existence of a norm may be clear to someone entering the situation, it is often less clear precisely what behavior is required in order to comply with the norm. We investigate how people react to uncertainty about the prevailing norm using a modified version of the dictator game. Since the behavioral effects of social norms are tightly linked to the degree of anonymity in a situation, we also vary the extent to which subjects' behavior is observable. We find that when behavior is anonymous, uncertainty about which norm guides partners reduces aggregate norm compliance. However, when others can observe behavior, introducing a small degree of norm uncertainty increases aggregate norm compliance. This implies that norm uncertainty may actually facilitate interaction as long as behavior is observable and uncertainty is sufficiently small. We also document that reactions to norm uncertainty are heterogeneous with one group of people reacting to norm uncertainty by increasing compliance (over-compliers), while another group reacts by reducing compliance (under-compliers). The main effect of increased observability operates through the intensive margin of the under-compliers; they reduce their negative reaction to norm uncertainty when their actions become more visible.
Keywords: C92; D9; 330; Social norms; Uncertainty; Audience